Family-Based Interventions in Preventing Transmission of Pulmonary Tuberculosis: A Cross-Sectional Study in Samarinda, Indonesia - Andi Lis G. Arming; Joko Sapto Pramono; Umi Kalsum; Askur (UPT Publikasi Ilmiah Universitas Islam Bandung, 2025)
Pulmonary tuberculosis (TB) remains a significant public health challenge in Indonesia, particularly in Samarinda, where transmission frequently occurs within family environments through close contact with infected individuals. Family-based interventions represent a critical component in enhancing preventive behaviors and reducing transmission risk, yet implementation of prevention efforts by family members of pulmonary TB patients remains suboptimal. This study aims to analyze the relationship between family roles and preventive behavior against pulmonary TB transmission in the working areas of the Karang Asam, Wonorejo, and Loa Bakung Health Centers in Samarinda. A cross-sectional research design with quantitative methodology was used. The sample consisted of 80 adult respondents, selected purposively from families of pulmonary TB patients living in the same household. Data collection was conducted between January and March 2025 using a structured questionnaire that measured the role of families and TB transmission prevention behaviors. Testing the instrument's validity and reliability is conducted before implementation. Statistical analysis uses the chi-square test to examine the relationship between variables. Statistical analysis revealed a significant relationship between family member roles and behavior aimed at preventing pulmonary TB transmission (p=0.001). Families demonstrating active preventive roles exhibited substantially higher implementation of prevention behaviors, including mask utilization, adequate household ventilation, and treatment adherence. The OR of 705.000 (95% CI=61.218–8,118.975) indicates families with good roles have a substantially greater likelihood of demonstrating effective TB prevention behaviors. In conclusion, family-based interventions are critical for preventing pulmonary TB transmission, with actively engaged families demonstrating superior implementation of preventive behaviors and reduced disease transmission risk within household environments.